Real-world impact of COVID-19 vaccination, household exposure, and circulating SARS-CoV-2 variants on infection risk and symptom presentation in a U.S./Mexico border community - Cohen, Ariel; Reyes, Breanna; Burola, Maria Linda; Lomeli, Angel; Escoto, Arleth A.; Salgin, Linda; Rabin, Borsika A.; Stadnick, Nicole A.; Zaslavsky, Ilya; Tukey, Robert; Laurent, Louise C.; Seifert, Marva (Frontiers in Public Health, 2025)
BackgroundSan Ysidro, a densely populated primarily Latino community near the U.S./Mexico border, reported the highest rate of COVID-19 infection in San Diego County. In this increased infection risk environment, we explored the impact of COVID-19 vaccine status, household exposure, and primary circulating SARS-CoV-2 variant on the probability of infection and symptom presentation while controlling for temporal and sociodemographic factors.MethodsData were collected as part of CO-CREATE (Community-Driven Optimization of COVID-19 Testing to Reach and Engage underserved Areas for Testing Equity), a collaborative implementation study between University of California San Diego, a local Federally Qualified Health Center, and the Global Action Research Center. Self-reported sociodemographic factors, household exposure, vaccine status, and symptoms were extracted from a cross-sectional questionnaire completed by participants; PCR test results were used for analysis. Multi-level logistic regression, to account for repeat testing, was used to estimate the impact of self-reported vaccination status on COVID-19 household transmission. Logistic regression was used to characterize symptoms associated with predominate circulating SARS-CoV-2 variants.ResultsBetween May 2021 and March 2023, 11,412 PCR test results from 6,032 participants were analyzed. Individuals who were vaccinated and had a household exposure were 3.5 times [aOR 3.5 (95% CI 2.7, 4.6)] more likely to be PCR positive compared to individuals who were vaccinated and reported no household exposure; and individuals who were unvaccinated and reported a household exposure were 9.1 times [aOR 9.1 (95% CI 5.3, 15.5)] more likely to be PCR positive compared to individuals who were vaccinated and reported no household exposure. These results were obtained after adjusting for variant wave, age, language spoken, previous infection status, symptom status, and employment. Symptoms varied by predominate circulating SARS-CoV-2 variant, highlighting the impact of variant on disease presentation and potential vaccine efficacy.ConclusionCOVID-19 vaccination was associated with a reduced risk of COVID-19 infection after household exposure, highlighting the importance of equitable access to COVID-19 vaccines, specifically in communities experiencing higher infection rates. Our findings also underscore the necessity for enhancing workplace safety protocols, addressing language-specific considerations, and being cognizant of differing symptom presentation by variant.